The influence of twinning reaction and attachment on identical young adult twins' identity formation. - Escanlar, Mayell Faith G.
This study was conducted for the purpose of determining how identical young adult twins develop individual identities in relation to their experiences of twinning reaction and attachment. Thematic analysis of the results revealed identical young adult twins exhibited twinning reaction through fusion of individualities, the inability to differentiate on from the other, having few opportunities for individual decision-making, and struggling over separation. on the other hand, their attachment functioned as motive to remain proximally close, as source of comfort and of assurance, and as a reason to keep their relationship healthy terms. Conversely, some twins claimed to be very distinct from one another or were non twinning and showed fractional importance for their relationship or were non-seeking. Twins furthermore placed varying levels of importance to the development of their individual identities in consideration for their personal drive, or lack thereof, towards independence and distinction. In addition, twins deemed their family, peers, proximity, and other non-twins to be the remain factors affecting their identity formation. A number of twins asserted that they formed some sense of individuality, while some claimed they have yet to do so.